PROFILE OF PROSTATE CANCER PATIENTS AT DR. MOEWARDI HOSPITAL PERIOD JANUARY 2017 – JANUARY 2022: RETROSPECTIVE STUDY - Sentoso, Joko Wibowo; Tusarawardaya, Setya Anton; Wibowo, Syaeful Agung (Indonesian Urological Association, 2024)
Objective: This study aims to know the profile of prostate cancer patients treated at Moewardi General Hospital from January 2017 to January 2022. Material & Methods: A retrospective study was conducted in prostate cancer patients who have or are undergoing therapy at Moewardi General Hospital from January 2017 to January 2022 using purposive sampling techniques. Results: From January 2017 to January 2022, 441 male patients were diagnosed with prostate cancer which is dominated able to go home alive, around 92.97%. The age of study subjects was overlooked of 70-80 years with a total of 182 people, dominated by self-employed as many as 420 people. The breakdown of PSA scores of 1-20 in as many as 247 people, Adeno Ca Prostate as many as 374 people with the majority of prostate Ca cases in subjects in non-metastatic status (359 people). The results of variable Rectal Toucher examination described results dominated by palpable prostate and hard as many as 437 people. Conclusion: The most important prognostic indicators in prostate cancer are the patient's age and general health at the time of diagnosis, the cancer stage, the level of pre-therapeutic PSA, and the Gleason score. A worse prognosis is associated with high levels of the disease, more advanced stages, younger age, and elevated levels of PSA. Keywords: Prostate cancer, patient’s age, PSA, male.